Orang Pesantren Di Dunia Politik (Studi Kasus Pesantren Miftahul Huda Manonjaya Tasikmalaya) - Nurjaman, Andri; Yusuf, Muhamad; Witro, Doli (Inovasi: Jurnal Diklat Keagamaan, 2021)
The debate about the involvement of Islamic boarding schools in the world of politics is in a tug of war, contradicting each other in the sense of experiencing pros and cons. Miftahul Huda Manonjaya Islamic Boarding School is one of the boarding schools in Tasikmalaya Regency, the founder of the Miftahul Huda Islamic Boarding School is late. K.H. Choer Affandi. There were 20 mandates that he left, one of which forbade him to enter the world of politics, but in the next reality, there were sons and grandsons of K.H. Choer Affandi who entered the world of politics. This article discusses Miftahul Huda Islamic Boarding School students who have entered politics, which seems to contradict one of Uwa Choer Affandi's mandates. This article aims to highlight the goals of Miftahul Huda Islamic boarding school students to enter the world of politics. This article uses qualitative research that is literature. The approach used is the theory of the relationship between religion and the state. The analytical technique used is the analysis technique popularized by Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results show that the Miftahul Huda Islamic Boarding School has succeeded in producing scholars as well as politicians whose main goals and motivations are Islamic da'wah, understanding the ahli sunnah wal jamaah, amar ma'ruf nahi munkar, and entering politics in the case of Miftahul Huda (as KH Asep Maoshul and Uu Ruzhanul Ulum) is a mandate from the Kyai Council and in order to carry out the mandate of the late. The main thing for Uwa Choer Affandi is to maintain the aqidah of the ahli sunnah wal jamaah and in the context of izatul Islam wal muslimun (the glory of Islam and the Muslims).